Preparation of future teachers of art disciplines for innovative activity in China - Jingqiu, Sun; Xiao, Tan; Yiping, Ji (Journal of Education, Health and Sport, 2020)
The article is devoted to substantiation of theoretical aspects of the problem of preparation of future teachers of art disciplines for innovative activity in China. The preparation of future teachers of art disciplines for innovation is considered by the authors as a system, as it can be described as an ordered set of interconnected components, which is a holistic formation. Among such components of the system are the purpose, content, methods, forms, means and so on. Readiness for innovative professional activity is considered by the authors as an integrative quality of personality, which is formed due to the emergence of a psychological system of activity, and its structure is identical to the structure of the corresponding functional psychological system. The components of such a system are the motives and goals of the activity, its information base and program, the decision-making unit and the subsystem of personality qualities, which is professionally important. It is proved that readiness and ability for innovative activity is provided by efficiency of introduction of the newest achievements of science, creative mastering of the advanced pedagogical experience of education, search of the most rational means of optimization of educational process and extracurricular activity of future teachers of art disciplines (group work, problem scientific groups, societies, etc).